(untitled) (Actualizaciones en Sida e Infectología, 2024)
Neisseria gonorrhoeae (NG) infection is considered a high public health priority because of its ability to develop resistance to most of the antibiotics used to treat it. The anorectal presentation is generally asymptomatic and frequent in men who have sex with men (MSM). In Argentina, dual therapy (ceftriaxone+azithromycin/doxycycline) is recommended as first line empiric therapy. This observational and retrospective study was conducted to evaluate the percentage of anorectal NG positivity, the susceptibility profile to penicillin, tetracycline, ciprofloxacin, ceftriaxone, cefixime and azithromycin, as well as the clinical-epidemiological aspects of patients attended between 20/10/2015 and 20/03/2020 in coloproctology of a public hospital. We detected 55/436 positive rectal swabs for NG (13%). 95% were MSM and 71% were PLHIV. In 18/55 NG was the only infection. The most frequent co-infections: HPV (38%) and C. trachomatis (35%). Susceptibility to extended-spectrum cephalosporins (ESCs) and azithromycin was 100% and 98%, respectively. Local emergence of the first five anorectal NG isolates with decreased susceptibility (DS) to ESCs, the first isolate with nonsusceptible category to azithromycin and another with DS to azithromycin concomitantly with DS to ESCs were observed. Although the use of dual empirical therapy continues to be adequate for our institution, the emergence of isolates with DS and NS to first-line drugs was observed, evidencing the importance of epidemiological surveillance at the local level to define empirical treatments